Effect of Ni content on the structural, morphological and magnetic properties of spray deposited Ni–Zn ferrite thin films. (July 2015) - Kumbhar, S.S.; Mahadik, M.A.; Mohite, V.S.; Hunge, Y.M.; Rajpure, K.Y.; Bhosale, C.H.
Graphical abstract: The Ni x Zn1− x Fe2 O4 (where x = 0.0, 0.2, 0.4, 0.6, 0.8, 1.0) thin films were prepared by spray pyrolysis technique onto the quartz substrates. The composition x = 0.4 shows the formation of the compact grain structure and highest saturation magnetization of 143 emu/cm 3 . Highlights: Synthesis of nanocrystalline Ni x Zn1− x Fe2 O4 thin films. Influence of Ni substitution on physicochemical properties. Electrical conductivity arises mainly from the grain boundary. The highest saturation magnetization is 143 emu/cm 3 for x = 0.4. Abstract: The Ni x Zn1− x Fe2 O4 thin films have been prepared using a simple spray pyrolysis technique. The X-ray diffraction studies reveal that, the films are polycrystalline with spinel structure. The lattice parameters vary in the range of 8.35–8.48 Å with composition ( x ) obeying Vegard's rule. SEM and AFM studies show that the surface of the films exhibit a smooth, compact and a pin hole free morphology. Raman spectra indicate first order Raman active modes; A1g ( λ = 334 cm −1 ); Eg ( λ = 148 cm −1 ) and T2g ( λ = 699) of the Ni x Zn1− x Fe2 O4 . The investigation on dielectric constant, dielectric loss tangent and ac conductivity was carried out in the frequency range 20 Hz–1 MHz at room temperature. The linear nature of the AC conductivity shows small polaron type of hopping mechanism. The saturation magnetization increases up to x = 0.4 (143 emu/cm 3 ), which decreases for higher x .